The Impact of External Auditor Forensic Accounting Competencies on Financial Performance of Listed Companies on the Indonesia Stock Exchange - Lukna, Yohanes Kevin; Miranda, Aqilah; Sihombing, Dona Olivia; Septika, Edya Nashwa; Larasasti, Sindy; Azzahra, An Suci (Pusat P2M Politeknik Negeri Batam, 2025)
As business complexity and financial fraud risks grow, external auditors play an increasingly vital role in maintaining the integrity of financial statements. Competencies such as forensic accounting are believed to enhance audit quality by strengthening fraud detection and prevention. Therefore, this study examines the impact of External Auditor Forensic Accounting Competencies (EAFAC) on the financial performance of companies listed on the Indonesian Stock Exchange in 2024. Using a quantitative approach, the research analyzes data from 282 companies selected through simple random sampling. Company size, leverage, and company age are included as control variables, and the data are analyzed using multiple linear regression in SPSS. The results show that, both partially and simultaneously, all variables have a significant effect on financial performance. Specifically, EAFAC and company size have a positive effect, while leverage and company age have a negative effect. Overall, these findings confirm that implementing forensic accounting competencies within external audit practices is a strategic investment to improve company financial performance, especially through more effective risk mitigation and fraud prevention. However, the research also identified challenges in implementing these competencies, especially within the Big Four public accounting firms, indicating room for further improvement and standardization in Indonesia’s audit profession.